THE INFLUENCE OF PERSONALITY ON PREMARITAL SEX BEHAVIOUR ON THE STUDENTS OF GRADE XI SCIENCE MAJORS OF PUBLIC HIGH SCHOOL IN GUNUNGKIDUL DISTRICT VIEWED FROM BIGFIVE - Nurul Adiningtyas; Popi Avati (Universitas Mercu Buana Jakarta, 2019)
One of the factors that influence sexual behavior is personality. The personality type that used in this research is personality with five dimensions (big five) namely openess to experience, conscientiousness, extroversion, agreeableness, and neuroticism. The objective of this research is to aims to determine whether there is influence between the Personality (Bigfive) to Sexual Behavior premarital students of class XI senior high school science major in Gunungkidul Regency. The research approach used is quantitative approach. The sample of this research is adolescents aged 15-19 years old who are classified in grade XI high school students science majors Gunungkidul Regency as many as 276 respondents with male samples of 84 students and 192 female students. Sampling method used is stratified sampling technique with cross sectional approach, with α = 0.05. Data collection using research instrument in the form of questionnaire, with the help of statistical application program in data processing, with sig value> 0.05. Based on the results of statistical analysis, the results of the analysis of the influence of Personality (Bigfive) with premarital sex behavior, from the analysis results obtained that of the six proposed variables there are two of which are accepted and four of them rejected. Personality (Bigfive) dimensions Neuroticsm (P = 0.553), Extraversion (P = 0.094), Openness (P = 0.090), gender (P = 0.713) rejected, while Agreableaness (P = 0.017), Conscientiousnes (P = 0.002) accepted , Overall from the results of the variable test states that there is influence between personality (Bigfive) on premarital sex behavior in the students of grade XI natural State Senior High School in Gunungkidul Regency at 8.1%. Researchers suggest that schools may consider planning for guidance on sex education, in order to prevent negative premarital sexual behavior.